2020
DOI: 10.1016/j.annonc.2020.08.1337
|View full text |Cite
|
Sign up to set email alerts
|

1945P Distribution of anti-PD1/PDL1 autoantibodies in multiple cancer types and potential biomarker role for anti-PD1 therapy

Abstract: Background: The blockade of entering the cell cycle represents a hallmark of chemoresistant cancer cells, especially in chemoresistant cancer stem cells. Cell cycle blockade in quiescent cancer (stem) cells is largely attributed to the natural dormant behaviour of stem cells, and in a natural state the quiescent stem cells respond to stimuli rapidly for activation. Thus, eliminating quiescent chemoresistant cancer (stem) cells by extrinsic stimuli that promote entry into cell cycle provides a potential strateg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Immunotherapy against targets such as Programmed Cell Death 1(PDCD1, PD-1) has recently been reported to be successful in the treatment of a variety of tumors [9][10][11][12][13][14][15][16]. With the deepening of research, TNBC has been found to have a higher rate of tumor immune invasion and mutation than other types of BC [17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…Immunotherapy against targets such as Programmed Cell Death 1(PDCD1, PD-1) has recently been reported to be successful in the treatment of a variety of tumors [9][10][11][12][13][14][15][16]. With the deepening of research, TNBC has been found to have a higher rate of tumor immune invasion and mutation than other types of BC [17][18][19].…”
Section: Introductionmentioning
confidence: 99%